Rekontekstualisasi Pancasila dalam Kehidupan Kewarganegaraan Modern: Studi Naratif terhadap Siswa SMP Negeri 18 Tangerang Selatan - Kurnia, Heri; Susi, Susi; Setiawati, Setiawati; Sasmita, Saepudin Karta (Journal of Civic Education, 2025)
Concerned by the erosion of civic values, this study investigates how Pancasila principles can be recontextualized and integrated into modern civic life among Indonesian youth. The research aimed to assess the understanding, perception, and practical application of these foundational principles by junior high school students. Employing a qualitative, narrative design, the study was conducted at SMP Negeri 10 Tangerang Selatan, involving 45 students across grades VII-IX. Data was collected over four months (August–November 2025) through in-depth interviews, focus group discussions, observations, and analysis of student reflective journals. Findings indicate a gap between theory and practice: 78% of students showed strong theoretical comprehension, but only 52% effectively applied these values in practical civic behaviors. Key challenges included translating values into digital-age realities and applying the principles of Just and Civilized Humanity (social media ethics) and Democracy (school participation). The study concludes that successfully recontextualizing Pancasila requires innovative, experiential pedagogical approaches, peer mentoring, and technology-integrated civic education to bridge abstract principles with contemporary youth experiences.